Enhancing color tunability, corrosion resistance, and hardness of AlN/Al coatings on magnesium alloys via sputtering a Si interlayer. (March 2023) - Shi, Xunwang; Zhang, Sam; You, Yuhang; Sun, Deen; Yu, Xiuhan; Wang, Jinbiao; Du, Hongji; Li, Fengji
Abstract: Synthesizing structural color coatings on magnesium alloys remains challenging. As inspired by the interference effect of visible light, this work sputtered a layer of Si on the Al bonding layer as the reflection layer followed by the deposition of AlN layer as the refraction layer. The influence of the Si interlayer on the morphology, structure, composition, color, corrosion resistance, and hardness of the AlN/Si/Al coatings was investigated systematically. With the introduction of the Si interlayer, the average grain size of AlN decreased from 19.3 to 16.7 nm, the surface roughness in Rq reduced from 13.6 to 11.2 nm, and the color of the coatings changed from silvery white to yellowish. The AlN/Si/Al-coated Mg alloys respectively displayed purple, indigo, blue, green, yellow, orange and red colors as the AlN surface layer thickness increased from 165 to 180, 200, 220, 250, 270 and 290 nm. Meanwhile, introducing the Si interlayer significantly improved the corrosion resistance and hardness of the coatings. The corrosion current density decreased from 1.5 × 10 −5 to 2.43 × 10 −6 A/cm 2, and the hardness doubled from 4.3 to 9.2 GPa. The mechanisms for color-tunning, corrosion resistance, and hardness enhancement were discussed in detail. Highlights: The color of AlN/Al-coated AZ31B Mg alloy could be tuned by introducing Si interlayer. The AlN/Si/Al coating could display different color via changing the AlN layer thickness. The AlN/Si/Al-coated AZ31B Mg alloy exhibits excellent corrosion resistance and hardness.